2022
DOI: 10.3390/ijms232415479
|View full text |Cite
|
Sign up to set email alerts
|

The Role of microRNAs in Inflammation

Abstract: Inflammation is a biological response of the immune system to various insults, such as pathogens, toxic compounds, damaged cells, and radiation. The complex network of pro- and anti-inflammatory factors and their direction towards inflammation often leads to the development and progression of various inflammation-associated diseases. The role of small non-coding RNAs (small ncRNAs) in inflammation has gained much attention in the past two decades for their regulation of inflammatory gene expression at multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 195 publications
0
31
0
Order By: Relevance
“…The miRNAs usually result in either translational repression or the degradation of the target mRNA (via binding to specific sequences at the 3′-UTR) or the inhibition of gene expression (via binding to either the 5′-UTR or the coding region of the target molecules). In contrast, their binding at the promoter site of the target molecules enhances gene expression [ 66 ]. In summary, a single miRNA could potentially target numerous mRNAs, while at the same time, one mRNA could contain multiple binding sites for miRNAs, turning this into a possibility that a vast number of biological processes could be regulated by this interaction [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…The miRNAs usually result in either translational repression or the degradation of the target mRNA (via binding to specific sequences at the 3′-UTR) or the inhibition of gene expression (via binding to either the 5′-UTR or the coding region of the target molecules). In contrast, their binding at the promoter site of the target molecules enhances gene expression [ 66 ]. In summary, a single miRNA could potentially target numerous mRNAs, while at the same time, one mRNA could contain multiple binding sites for miRNAs, turning this into a possibility that a vast number of biological processes could be regulated by this interaction [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Colitis [42] miR-21 A negative regulator of IRAK1 and MyD88 in the TLR signaling pathway HCV infection [43] miR-146a Regulates the release of IL-1β, IL-6, and TNF-α [44] miR-Inhibits the production of inflammatory factors such as IL-1β, IL-6, and TNFα [45] let-7 Overexpression led to reduction in IL-6, IL-8, and TNFα COVID-19 [46] Modulates ICAM1, IL-1β, TNF-α, and IFN-γ secretion Diabetes-associated atherosclerosis [47] miR-Upregulation of miR-150-5p alleviates LPS-induced inflammatory response by targeting Notch1 [48] Regulates the inflammatory response in macrophages by STAT1 [49] miR-7 IL-1β reduces the level of miR-7, thereby increasing the expression of CD98 IBD [50] miR-Upregulation was associated with a significant decrease in NF-kB [51] (Continues) miR-10a can regulate various inflammation-associated diseases such as rheumatoid arthritis (RA), inflammatory bowel disease (IBD), colitis, acute pancreatitis (AP), sepsis, atherosclerosis, and cancer. 56 The downregulation of miR-10a is accompanied by the induction of IL-12/IL-23p40 and colitis in mice. 42 The miR-181 family (miR-181a, miR-181b, miR-181c, and miR-181d) negatively regulates TNFα mRNA stability.…”
Section: Main Functions Disease Referencesmentioning
confidence: 99%
“…In the last few years, miRNA as a non‐coding RNA has been elucidated in the pathogenesis of SJS/TEN and investigated as a potential diagnostic marker for SJS/TEN. MiRNA can regulate the expression of cell‐secreted inflammatory mediators in PBMC 10 . A few studies indicated that aberrant expression of miRNAs in the skin and serum of SJS/TEN.…”
Section: Introductionmentioning
confidence: 99%
“…MiRNA can regulate the expression of cell-secreted inflammatory mediators in PBMC. 10 A few studies indicated that aberrant expression of miRNAs in the skin and serum of SJS/TEN. More importantly, Ichihara and Sato established that miR-18a-5p and miR-124 upregulation could be used as markers for TEN disease assessment.…”
Section: Introductionmentioning
confidence: 99%